Dampak Teknologi Digital Terhadap Pembentukan Karakter Islami Peserta Didik di Era Society 5.0 - Akramul Insan Zaer; Misra Misra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In the era of Society 5.0, the rapid advancement of digital technology has had a significant impact on the world of education, including the process of character development in students. On one hand, technology makes access easier to innovative and interactive Islamic educational resources. On the other hand, this progress has also caused a decline in moral values due to exposure to digital content that is inconsistent with Islamic teachings. The objective of this research is to examine how digital technology affects the formation of Islamic character in students. Additionally, this study investigates the most suitable Islamic educational methods to address this issue. This research was conducted qualitatively using a literature study approach and utilizing various relevant literature and scholarly journals. The results indicate that if used correctly and purposefully, digital technology can assist in Islamic character education. Therefore, collaboration between educators, parents, and educational institutions is essential in integrating Islamic values into digital learning media so that the character formation of students remains in accordance with Islamic teachings.